'The Birth of the Virtual Choir': Exploring the multimodal realisation of the Covid-19 liminal space in a YouTube virtual choir performance. Issue 2 (June 2022) - Kerry, Victoria J
As countries around the world went into lockdown in 2020 during the Covid-19 pandemic, people looked for virtual ways of reducing social isolation. Amongst these online interactions, a relatively new phenomenon – the virtual choir – grew in popularity. As part of a wider study on virtual choirs, this study analyses the multimodal performance of, and textual audience responses to, 'The Birth of the Virtual Choir', posted on YouTube in June 2020. The study uses a combination of Mediated Discourse Analysis (Norris and Jones, 2005) and the theoretical concept of liminality (Turner, 1974; van Gennep, 1960) as a means of understanding how one performance in this new genre was used to reflect personal crises during the pandemic and enforced lockdowns. It argues that the song mirrors a process of separation, transition and reaggregation in both time and space, consistent with rites of passages and liminal experiences, whereby social actors are isolated, use creative ways to find order to the chaos, then reintegrate into society as changed subjects. It also demonstrates how online creativity and illusion highlighted one choir's experience on life and lockdowns during the Covid-19 pandemic, many of which appeared to ring true for their wider audience and other virtual choirs being born into the Covid era.